2015
DOI: 10.17687/jeb.0301.01
|View full text |Cite
|
Sign up to set email alerts
|

Financial access for starting a business: Evidence of internal and external financial sources, and performance of Malaysian SMEs

Abstract: The main objective of this study is to unearth the impact of internal and external funding sources for starting a business on the performance of SMEs, and to identify the potential of other core variables namely business experience, educational level, and size of firm, which may significantly influence the SMEs' performance. The data was collected from 484 SMEs via a structured questionnaire and analyzed by using the Structural Equation Modeling (SEM) technique. The study found that the internal and external s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Conversely, Ayyagari et al (2010), Klapper et al (2006), Ayyagari et al (2011) and Beck et al (2005) found that improved access to formal finance correlates with faster firm growth, promotes new entrance and enhances rapid innovation and dynamism among firms. Mohamad et al (2015) employed structural equation modelling to examine the relationship between firm performance and internal and external sources of finance in Malaysia and found that internal and external sources of finance have no significant effect on SMEs' performance. However, business experience, level of education and firm size have a positive effect on performance.…”
Section: Performance Of Msmes In Eswatinimentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Ayyagari et al (2010), Klapper et al (2006), Ayyagari et al (2011) and Beck et al (2005) found that improved access to formal finance correlates with faster firm growth, promotes new entrance and enhances rapid innovation and dynamism among firms. Mohamad et al (2015) employed structural equation modelling to examine the relationship between firm performance and internal and external sources of finance in Malaysia and found that internal and external sources of finance have no significant effect on SMEs' performance. However, business experience, level of education and firm size have a positive effect on performance.…”
Section: Performance Of Msmes In Eswatinimentioning
confidence: 99%
“…Mohamad et al. (2015) employed structural equation modelling to examine the relationship between firm performance and internal and external sources of finance in Malaysia and found that internal and external sources of finance have no significant effect on SMEs' performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Por outro lado, a de se considerar que os APLs são compostos, em sua maioria, por pequenas empresas (SIMONETTI; KAMIMURA; OLIVEIRA, 2015), e que a continuidade empresarial desses negócios depende do acesso a fontes externas de financiamento. Sobre esse assunto, Cerbusca (2015) argumenta que, em sua fase inicial de funcionamento, as pequenas e médias empresas contam principalmente com fontes internas de financiamento, contudo, quando o custo de crescimento dessas empresas ultrapassa a disponibilidade de recursos financeiros dos proprietários, esses empreendimentos passam a depender de fontes externas de financiamento (HUSSAIN; MILLMAN;MATLAY;2006), que assumem papel de destaque na produtividade e crescimento desses negócios (MOHAMAD et al, 2015).…”
Section: Arranjo Produtivo Local (Apl) Pequena Empresa E Financiamentounclassified
“…The main sources of external financing offered in Malaysia come from financial institutions, namely Banking Institutions (BIs) and the Development Financial Institutions (DFIs) (Mohamad et al, 2015). Unfortunately, it is often not readily accessible for SMEs as financial institutions provide financing for businesses particularly successful ones and those which continue to grow (Abdesamad and Wahab, 2014).…”
Section: Youth Entrepreneurs and Sources Of Financingmentioning
confidence: 99%